2020
DOI: 10.3389/fphy.2020.527394
|View full text |Cite
|
Sign up to set email alerts
|

Wide-Angle Circular Polarization Converter Based on a Metasurface of Z-Shaped Unit Cells

Abstract: Since it is designable, metasurface was widely used in various fields, especially the design of polarization converters. However, most of the polarization converters currently designed can only work under normal incidence or small angle incidence, which hugely limits the application of the device. In this paper, a chiral metasurface based on the z-shaped unit cell, which can manipulate circular polarization wave, is proposed. The simulation result shows that this converter can maintain the polarization state o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…To date, several systems based on metasurfaces have been proposed to control the polarisation of an EM wave both in terms of Linear-to-Linear (LP-to-LP) and Linear-to-Circular (LP-to-CP) conversion [11]. With this regard, polarization control can be achieved via resonating [12], anisotropic [13], chiral [14] and artificial magnetic conductor [15] elements, both in transmission and reflection modes [16]. Notably, LP-to-LP [17] and LP-to-CP [18] ultra-wideband conversions have been demonstrated relying on anisotropic metasurfaces.…”
Section: Introductionmentioning
confidence: 99%
“…To date, several systems based on metasurfaces have been proposed to control the polarisation of an EM wave both in terms of Linear-to-Linear (LP-to-LP) and Linear-to-Circular (LP-to-CP) conversion [11]. With this regard, polarization control can be achieved via resonating [12], anisotropic [13], chiral [14] and artificial magnetic conductor [15] elements, both in transmission and reflection modes [16]. Notably, LP-to-LP [17] and LP-to-CP [18] ultra-wideband conversions have been demonstrated relying on anisotropic metasurfaces.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that a properly designed metasurface has a great potential of converting a given polarization into other polarization types (e.g., circular and elliptical) with the benefits of inexpensive profile and light weight [14,15]. Although broadband linear polarization (LP) [16], circular polarization (CP) [17], and effective narrow-band [18,19] conversions have been performed partly in existing studies, to the best of our knowledge, there is no polarization converter with the features of ultra-thin and oblique-angle independence capable of simultaneously utilizing the polarization types of both linear and circular polarized waves operating at C-(4-8 GHz), X- (8)(9)(10)(11)(12), and Ku-bands (12)(13)(14)(15)(16)(17)(18). Therefore, multiband devices are in high demand.…”
Section: Introductionmentioning
confidence: 99%
“…Reflective polarization converters are known for their advantageous energy efficiency compared with their transmission-based counterparts. Researchers have explored a variety of structures in this category, including the cut-rhombus shape 27 , 8-shaped 28 , L-shaped 29 , double-square-shaped 30 , Z-shaped 31 , and ellipse-shaped 32 , all of which have demonstrated the potential for achieving polarization conversion through reflection. However, it is important to recognize the challenges in this area.…”
Section: Introductionmentioning
confidence: 99%